The Effect of Nutrients Mixture on The Biomass and Lipid Production from Microalgae Botryococcus braunii Mutated by UV-C Rays - Thea Prastiwi Soedarmodjo; Hakun Wirawasista Aparamarta; Arief Widjaja (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2021)
Nutrient is one of the most important factors in the growth of microalgae. This research was conducted to study the effect of nutrient mixture on the biomass and lipid production of Botryococcus braunii. Microalgae B. braunii was cultivated in the commercial nutrient medium of agricultural fertilizer combinations of ammonium sulphate (ZA), urea, and triple superphosphate (TSP). Before the cultivation process, B. braunii was exposed to UV-C rays (254 nm) for 3 minutes. The concentration and type of fertilizer as a nitrogen source divided into four types of mixtures, namely FM-1, FM-2, FM-3, and FM-4 were compared with Walne nutrients to study their effects on microalgae growth and lipids. FM-1 consisting of 150 mg/L of ZA, 7.5 mg/L of urea, and 25 mg/L of TSP led to the best growth for native and mutated microalgae strains compared to Walne nutrients and other nutrient mixtures. The mutated microalgae showed less growth than the native microalgae strains. However, the mutation process significantly increased the lipid content in the microalgae. In native microalgae strains, FM-4 consisting of 136.3 mg/L of urea and 50 mg/L of TSP produced the lowest lipid at 8.96%. After being exposed to UV-C rays, the lipids in FM-4 medium increased to 55.11%. The results show that the use of commercial fertilizers and exposure to UV-C rays on microalgae have high potential in preparing lipids as raw material for biodiesel which can be effectively applied in large-scale microalgae cultivation.